O bairro do Estácio de Sá e o Morro do São Carlos: lugares na cidade carioca sob os versos de Gonzaguinha - Moreira, Daniel Barreto de Barros (Universidade Federal de São Carlos, 2024)
Gonzaguinha was an artist whose experiences in Rio de Janeiro's Estácio de Sá neighborhood and on São Carlos Hill, coupled with his critical view of his lived reality, produced a significant musical legacy within Brazilian Popular Music (MPB). His unyielding connection to these places — as a boy from the favelas —was something he constantly recalled and emphasized.These early experiences formed the foundation of his artistic identity, earning him the nicknames "the street kid" or "the boy from the hill." After all, there were many challenges to overcome and confront. This context raises several questions: What was the essence of these places, and how did their unique character shape the music created by this artist? Our goal is to explore the relationship between Gonzaguinha's surroundings—specifically, Rio de Janeiro's Estácio neighborhood and São Carlos Hill during the first half of the 20th century—and the geographic context of this urban space.To achieve this, we analyzed Gonzaguinha's interviews, testimonials, lyrics, and songs, contextualizing them within our research on Rio's urban landscape and the distinct identity of the Estácio neighborhood. This analysis was informed by the ideas of Milton Santos and Ana Fani Carlos. Our findings reveal how the characteristics of these environments shaped Luiz Gonzaga Jr.'s artistic style, and conversely, how his music reflects a deep spatial understanding of his surroundings. This makes his work a valuable resource for analyzing urban spaces.
El barrio de Estácio de Sá y el Morro de São Carlos: lugares en la ciudad carioca bajo los versos de Gonzaguinha
Keywords: Espaço Urbano; Lugar; Gonzaguinha; Bairro do Estácio de Sá; Urban Space; Estácio de Sá Neighborhood; Place; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA::GEOGRAFIA URBANA